Great 'app‐eal' but not there yet: A review of iPhone nutrition applications relevant to child weight management. Issue 4 (16th April 2015) - Burrows, Tracy L.; Khambalia, Amina Z.; Perry, Rebecca; Carty, Danika; Hendrie, Gilly A.; Allman‐Farinelli, Margaret A.; Garnett, Sarah P.; McNaughton, Sarah A.; Rangan, Anna M.; Truby, Helen; Collins, Clare E.; Golley, Rebecca K.
Abstract: Aims: There is increasing interest in the use of smartphone applications (apps) for delivering child obesity management interventions and supporting lifestyle behaviour change; however, there has been very little academic research on their development. Our aim is to review nutrition‐related apps designed for children currently available in Australia for their usefulness in education or support behavioural interventions for child obesity. Methods: Apps available for download in iTunes Australia between 2 April and 3 June 2013 which were suitable for children >12 years were identified. Key words were chosen to identify apps applicable to children, focusing on nutrition. Results: A total of 27 apps were included. Most apps (24/27) were not based on evidence‐informed recommendations. A third of apps were developed in the USA (n = 10; 37%) and were free (67%), nine apps required upfront payment, with a mean cost of A2.80 (range A0.99–A7.49). The most common nutrition features were the promotion of energy balance (n = 12 apps) and guidance on appropriate portion size (n = 15). The most common behaviour change feature was goal setting (n = 15). The five apps that scored most highly against the characteristics reviewed were: Calorie Counter Pro by My Net Diary, Weight Watchers, Swap It Don't Stop It, Control My Weight by CalorieKing and Rate What I Ate—Photo Diet Tracker. Conclusions: Very few apps were identified that could be used in education or support behavioural interventions for child obesity. There is a need to harness this technology and evaluate the applicability and use within childhood obesity research interventions.